The Influence of Work Discipline and Work Environment on Performance with Job Satisfaction as a Mediator - Siti Nur Halisah Putri Wasch; Suyoto; Hermin Endratno; Arini Hidayah (MultiTech Publisher, 2025)
Education is one of the most important factors to advance a nation with a good level of education, it can prepare young people to become a superior generation to be able to contribute to development. The diversity of facilities, educators and work environments in these schools is a challenge for teachers and employees in improving performance. Field data shows that the number of teachers and employees is 134 people and 2,288 students. This study aims to determine the effect of work discipline and work environment on performance with job satisfaction as a mediating variable on teachers and employees of SMP Kalibagor District. This study uses quantitative methods, data were collected through questionnaires and analyzed using SEM-PLS. The results of the study showed that work discipline had a significant effect on performance, work discipline had no significant effect on job satisfaction, work environment had a significant effect on performance, work environment had a significant effect on job satisfaction, job satisfaction had a significant effect on performance, job satisfaction had no significant effect as a mediation between the work environment and performance, and job satisfaction had a significant effect as a mediation between work discipline and performance.